Still running fast: Plasmodium ookinetes and sporozoites 125 years after their discovery - Singer, Mirko; Frischknecht, Friedrich (Trends in parasitology, 2023)
Plasmodium ookinetes and sporozoites were discovered 125 years ago by MacCallum (J. Exp. Med. 1898;3:117-136) and Ross (Ind. Med. Gaz. 1899;34:1-3), respectively. While the migration capacity of ookinetes was noted immediately, the movements of sporozoites remained enigmatic for decades. Today, we know many proteins involved in parasite migration and start to conceptualize a mechanistic understanding of motility.